Abraham – a Canaanite? Tracing the Beginnings of the Literary Tradition of Abraham - Lemański, Janusz Adam (The Biblical Annals, 2021)
The objective of the article is to present the current state of discussion on the first literary version of the series about Abraham and its sources or roots. The current state of research suggests that the starting point of the literary version of the narrative about this patriarch may have been a kind of tradition associated with the local shrine in Mamre, near Hebron. The other theory describes the idea of the promise of a descendant in return for the extraordinary and extended hospitality towards God. More importantly, this tradition may have been connected with Abraham from the very beginning, but it does not necessarily have to have been. The first version of a longer narrative about Abraham was the cycle of Abraham – Lot – Sodom (Gen 18*–19*). An introduction to the cycle (Gen 13:5-13) was written, already including the content of the two chapters mentioned above. According to the original version of the cycle, Abraham is not yet closely related to Lot, but he is an autochthonous character. Obviously, the goal of the series remains the ethnogenesis of the inhabitants of Judah in relation to the neighbouring peoples (the Moabites and Ammonites). Moreover, the latter clearly form a negative contrast here – both ethnically and civilisationally. This version of the narrative can be dated back to the end of the 7th century before Christ. The subsequent extensions or enlargements were initially associated with the combining of the characters of Abraham and Jacob. Such a combination could have been achieved, amongst others, by identifying the descendant promised to Abraham with Isaac. The priestly tradition internationalised Abraham even more and thus made him a pilgrim who had come from Ur of the Chaldeans.